2018
DOI: 10.1109/tnet.2018.2878965
|View full text |Cite
|
Sign up to set email alerts
|

Low-Complexity Distributed Radio Access Network Slicing: Algorithms and Experimental Results

Abstract: Radio access network (RAN) slicing is an effective methodology to dynamically allocate networking resources in 5G networks. One of the main challenges of RAN slicing is that it is provably an NP-Hard problem. For this reason, we design near-optimal low-complexity distributed RAN slicing algorithms. First, we model the slicing problem as a congestion game, and demonstrate that such game admits a unique Nash equilibrium (NE). Then, we evaluate the Price of Anarchy (PoA) of the NE, i.e., the efficiency of the NE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 52 publications
0
46
0
Order By: Relevance
“…δ ξ ). Therefore, the training objective of Dirac-WGAN-GP is given by L(θ, ψ) = ψθ − ξψ (16) and the gradient penalty proposed in [35] is given by…”
Section: Discussionmentioning
confidence: 99%
“…δ ξ ). Therefore, the training objective of Dirac-WGAN-GP is given by L(θ, ψ) = ψθ − ξψ (16) and the gradient penalty proposed in [35] is given by…”
Section: Discussionmentioning
confidence: 99%
“…The above discussion suggests that the RAN slicing problem has diverse and generally opposing requirements. Recent research work has suggested to let MNOs handle the slicing request generation and MU scheduling and transmission phases, while leaving the network slicing generation phase to the IP [14]. Conversely, the network slicing generation phase is left to the IP which possess the global network view required to implement fine-grained RB allocation [13].…”
Section: Complexity Vs Optimality Vs Privacymentioning
confidence: 99%
“…Submission Interface (SI): the slicing requests generated by the Slice Request Generator block (Section III-C) are submitted to the IP through the SI. The design of the SI can rely upon web-based services [14] or client-based software with dedicated GUIs to facilitate the submission process [13].…”
Section: A the I/o Middleware Tiermentioning
confidence: 99%
See 1 more Smart Citation
“…This work borrows the slice resource provisioning approach introduced in [28], and adapts it to the joint radio and network infrastructure resource provisioning. Constraints related to the infrastructure network considered in [17,18,27,28] are combined with coverage and radio resource constraints introduced in [29,30,31,32].…”
Section: Main Contributionsmentioning
confidence: 99%